The Impact of Estrogen Levels on the Development of Breast Cancer in Postmenopausal Women with Diagnosed Obesity or Overweight - Pochopień, Jakub; Pograniczny, Mikołaj; Mielżyńska, Adrianna; Pacołta, Adrianna; Nalepka, Marcelina (Quality in Sport, 2026)
Breast cancer is one of the most commonly diagnosed malignancies in women. Its development is largely influenced by hormonal factors. Estrogens, as key female sex hormones, play a crucial role in the proliferation of mammary gland cells, which may contribute to the initiation and progression of tumorigenesis. In postmenopausal women, estrogens are primarily derived from the conversion of androgens in adipose tissue, leading to hormonal changes that impact breast cancer risk. This study aims to examine the influence of estrogen levels on breast cancer development in postmenopausal women with overweight and obesity, as well as to elucidate the underlying biological mechanisms of this association. The molecular actions of estrogens and their effects on estrogen receptor (ER) expression in the context of breast cancer will be discussed. Additionally, the role of obesity as a risk factor for breast cancer in postmenopausal women will be presented. This article seeks to enhance the understanding of the role of obesity in oncogenesis among women whose physiological estrogen levels should correspond to their age-appropriate hormonal balance.